Becoming the Eternal Subject of Death in Architecture: The Tomb of (The Mad) Husrev Pasha - Esma İgüs (Art-Sanat)
This article examined the tomb of (The Mad) Husrev Pasha, which is located in the neighborhood of Yenibahce in Istanbul. This tomb, designed by Mimar Sinan at the beginning of his professional career, is known as one of the oldest urban spaces in Istanbul. Dating back to the 16th century, it is unique in terms of its design and decoration. Previously, there was a bazaar, a school, and an Ottoman coffee house surrounding the tomb, but today, the monument is situated between buildings. Despite its importance, the monument has only been discussed in Ekram Hakke Ayverdi’s 1995 work about the architecture of Mimar Sinan titled, “the Tomb of Husrev Pasha,” and in the history of academic literature in Turkey. However, there are serious mistakes and ambiguous statements in these studies about the tomb itself and the date that it was built. Additionally, the mistakes and contradictory statements about the lodge that used to be located next to the tomb and whose presence was detected through old maps, manuscripts, and written sources, make it almost impossible to establish the correct spatial history of the tomb. Thus, Mimar Sinan’s creation of the Tomb of Husrev Pasha was analyzed from a monographic perspective, within the framework of art history and architectural history. Moreover, through the identification of the repeated historical and spatial errors in the various sources, this article formulates a correct inscriptiveconstruction by including personal and judicial archives as well as timely sources regarding the tomb in the architectural historiography.